Therapeutic perspectives of p ‑coumaric acid: Anti‑necrotic, anti‑cholestatic and anti‑amoebic activities - Muruato, Liseth Rubi Aldaba; Juarez, Javier Ventura; Hernandez, Alan Michael Perez; Morales, Alejandro Hernandez; Ortega, Ma; Hernandez, Sandra Luz Ma; Sanchez, Brendaalvarado; Perez, Jose Roberto Macias (World Academy of Sciences Journal, 2021)
Phenolic acids are phytochemical compounds derived from plant biomass materials, that have notable health benefits with high therapeutic potential in several diseases. p-coumaric acid (p-CA) is a phenolic acid that displays various biological activities, such as antioxidant, anti-inflammatory, analgesic and anti-antimicrobial properties. However, the ability of p-CA to prevent hepatic necrosis and cholestasis induced by various harmful agents has not yet been explored to date, at least to the best of our knowledge, and there is no evidence that p-CA exerts an anti-parasitic effect. Therefore, the present study employed male Wistar rats, and the study was divided into two experimental in vivo parts. A liver necrosis model was established using carbon tetrachloride (CC[l.sub.4]) for 24 h, and a cholestasis model induced by common bile duct ligation (BDL) for 48 h was also established. On the other hand, the Entamoeba histolytica HMLIMSS strain was used as in vitro model employing Trypan blue cell viability assay. The results revealed that p-CA treatment significantly reduced the levels of the necrosis biomarker, alanine aminotransferase, and completely prevented the increase in the levels of the cholestasis markers, alkaline phosphatase and [gamma]-glutamyl transpeptidase in rats intoxicated with CC[l.sub.4] as well as in those subjected to BDL. Macroscopic observations and the hematoxylin and eosin staining results were consistent with the biochemical determinations, providing evidence of the hepatoprotective effects of p-CA. Moreover, 500 [micro]M p-CA inhibited the growth of Entamoeba histolytica, 26.5% at 12 h and 41.5% at 24 h compared with the controls. Thus, to the best of our knowledge, these findings provide the first evidence that p-CA prevents liver damage induced by CC[l.sub.4] or BDL (necrosis and cholestasis) and exhibits amoebostatic activity against Entamoeba histolytica. Key words: amoebiasis, cholestasis, Entamoeba histolytica, necrosis, p-coumaric acid